Transcription Profiling of Rice Panicle in Response to Crude Toxin Extract of Ustilaginoidea virens - Fu, Rongtao; Chen, Cheng; Wang, Jian; Liu, Yao; Zhao, Liyu; Lu, Daihua (Frontiers in Microbiology, 2022)
Ustilaginoidea virens infects rice, causing rice false smut disease and reduced yields. During its growth, U. virens can also produce some toxins but little is known about the response mechanisms of the plant to U. virens toxins. U. virens toxins can inhibit the accumulation of total sugar in rice panicles. We used RNA sequencing to analyze the differential expression profile induced by infiltrating crude toxins into early growth–stage rice panicles. We compared the transcriptomes of the control and crude toxin–treated rice panicles and determined variable transcriptional responses under the action of the crude toxins. A total of 6,127 differentially expressed genes (DEGs) were identified. Among these genes, 3,150 were upregulated and 2,977 were downregulated. Gene Ontology (GO) and metabolic pathway enrichment analyses indicated that U. virens toxins mainly influenced glycometabolism, amino acid metabolism, and secondary metabolism of rice panicles. DEG analysis showed that the gene expression levels of 10 transcription factor families were significantly changed. Genes involved in phenylpropanoid biosynthesis, flavonoid biosynthesis, sugar transporters, and starch synthesis–related were significantly downregulated, including cytochrome P450, beta-glucosidase, CHS1, sucrose transporters, SWEETs, starch-branching enzymes, and UDP-glucose pyrophosphorylase. However, genes involved in programmed cell death (PCD) were significantly upregulated, and contained cytochrome c, metacaspase, and protein kinase genes. The results indicate that U. virens toxins may act as pathogenic factors to reduce stress resistance, disrupt total sugar accumulation and starch formation, and induce PCD.